134 The efficacy of a Buttiauxella sp. phytase relative to diets with graded levels of inorganic phosphate in piglets. (5th December 2019) - Lizardo, Rosil; Velayudhan, Deepak E; Villca, Boris; Marchal, Leon; Dersjant-Li, Yueming
Abstract: The effect of a Buttiauxella sp. phytase on performance and bone ash in piglets was evaluated. A negative control (NC) diet was formulated without inorganic phosphate [0.11% digestible phosphorus (P)] and lower in calcium (Ca, 0.5%). NC was supplemented with the phytase at 0, 500 and 1, 000 FTU/kg diet or with mono-calcium phosphate (MCP) at 4 levels to add 0, 0.7, 0.14 and 0.18% digestible P and with additional limestone to maintain Ca to P ratio (1.2 to 1.3). The latter was the positive control (PC) and contained 0.7% Ca and 0.29% digestible P, meeting NRC requirement. A total of 108 Pietrain × (Landrace × Yorkshire) piglets were fed adaptation diets from 21 (weaned) to 42 d of age. Then, they were divided into 9 blocks according to body weight (BW) (9 replicates/treatment, mean initial BW 10.2 kg, mixed sex) and allocated at 2 piglets per pen. Piglets were fed mash test diets (based on corn, soybean meal with broken rice, rice bran and sugar beet pulp) ad lib for 28 d. At the end, 1 piglet per pen was euthanized and the right foot collected to determine metacarpal ash, Ca and P content. Data were analyzed using JMP 14.0. The NC reduced (P < 0.05) average daily gain (ADG), average daily feed intake (ADFI), bone ash, Ca and P, and increased feed conversion ratio (FCR) vs PC (Table 1). Increasing phytase and MCP linearly increased (P < 0.05) ADG, bone ash, Ca and P and reduced FCR. Linear regression analysis using increasing digestible P from MCP as reference indicated that phytase at 1, 000 FTU/kg can replace 0.16, 0.18 or 0.16% digestible P from MCP, using bone ash, ADG or FCR as response parameter, respectively. In conclusion, Buttiauxella phytase improved performance and bone ash in piglets fed diet without added inorganic phosphate.